When Women's Work Disappears: Marriage and Fertility Decisions in Peru - Hani Mansour; Pamela Medina; Andrea Velásquez (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the gendered labor market and demographic effects of trade liberalization in Peru. To identify these effects, we use variation in the exposure of local labor markets to import competition from China based on their baseline industrial composition. On average, the increase in Chinese imports during 1998-2008 led to a persistent decline in the employment share of low-educated female workers but had smaller and transitory effects on the employment of low-educated men. In contrast to the predictions of Becker's model of household specialization, we find that the increase in import competition during this period increased the share of single low-educated people and decreased their marriage rates. There is little evidence that import com-petition affected fertility decisions. The results highlight the role of gains from joint consumption in marriage formation.
Keywords: J16; J12; J13; J23; 330; import competition; marriage formation; fertility